RASP 4: Ancestral State Reconstruction Tool for Multiple Genes and Characters. (31st October 2019) - Yu, Yan; Blair, Christopher; He, Xingjin
Abstract: With the continual progress of sequencing techniques, genome-scale data are increasingly used in phylogenetic studies. With more data from throughout the genome, the relationship between genes and different kinds of characters is receiving more attention. Here, we present version 4 of RASP, a software to reconstruct ancestral states through phylogenetic trees. RASP can apply generalized statistical ancestral reconstruction methods to phylogenies, explore the phylogenetic signal of characters to particular trees, calculate distances between trees, and cluster trees into groups. RASP 4 has an improved graphic user interface and is freely available from http://mnh.scu.edu.cn/soft/blog/RASP (program) and https://github.com/sculab/RASP (source code).